1982
DOI: 10.1159/000182646
|View full text |Cite
|
Sign up to set email alerts
|

Citrate in Urine and Serum and Associated Variables in Subgroups of Urolithiasis

Abstract: Outpatient renal stone formers belonging to the established urolithiasis subgroups and controls were examined with respect to urinary and serum citrate (Cit) and several associated variables. Only in the normocalciuric majority of calcium and in uric acid stone formers was Cit in 24-hour urine decreased, but was normal in 2-hour fasting morning, and in 3-hour postprandial urine following a Cit-free test meal. Serum Cit was elevated in normocalciuria, renal and resorptive hypercalciuria. This Cit constellation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
1

Year Published

1987
1987
2007
2007

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(23 citation statements)
references
References 29 publications
2
20
1
Order By: Relevance
“…Citrate excretion in human beings results from a very complex renal handling which is, in turn, influenced by acid-base or potassium balance-related factors [5,7,12,15,16]. Since renal insufficiency is quite constantly asso ciated with derangements in both acid-base and potas sium balances, the changes induced by the impairment of renal function appear to be poorly predictable.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Citrate excretion in human beings results from a very complex renal handling which is, in turn, influenced by acid-base or potassium balance-related factors [5,7,12,15,16]. Since renal insufficiency is quite constantly asso ciated with derangements in both acid-base and potas sium balances, the changes induced by the impairment of renal function appear to be poorly predictable.…”
Section: Discussionmentioning
confidence: 99%
“…Citrate excretion results from a complex renal handling, which involves complete glomerular filtration, extensive reabsorption along the renal tubule, and specific metabolic processes in the tubular cells [4,5]. Due to its role in the pathogenesis of calcium stone disease, patterns of citrate excretion and their dependence on acid-base balance-related fac tors have been widely investigated in healthy subjects and stone-forming patients [6][7][8][9]. It is currently agreed that acid-base status [10,II] and potassium balance [12] are the major determinants of citraturia, and that changes in fractional excretion account for most of the variation in urine citrate [4,5,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypocitraturia is known to occur when there is overt deficiency of either potassium or magnesium, probably as a result of potassium-induced intracellular acidosis (Fourman and Robinson, 1953;Rudman et at., 1980;Simpson, 1983;Schwille et at., 1982). Marangella and Linari (1987) observed that urinary potassium was lower in hypocitraturic stone formers than it was in normocitraturic stone formers.…”
Section: Discussionmentioning
confidence: 99%
“…This could explain its infl uence on both crystal growth and aggregation [19]. Hypocitraturia in stone formers has been reported more frequently, some studies show that citrate excretion in stone formers is different from that observed in healthy subjects [20][21][22]. A signifi cant number of data seem to indicate that citrate excretion is a signifi cant determinant of stone formation, consequently diet supplementation with citrate has become a widespread form of prophylaxis and therapy [23].…”
Section: Current Knowledgementioning
confidence: 99%